(untitled) (Филолошки студии, 2020)
The subject of the paper is the gender marked conceptual metaphor WOMAN IS A BIRD in two closely related languages − Bulgarian and Croatian languages. The corpus of analyzed ornithonyms, which are metaphorically used for a female referent, was collected from general monolingual and phraseological dictionaries, as well as online and slang dictionaries. Some meanings were illustrated by examples from the online corpora hrWac and Bulgarian web 2012 through the use of the Sketch engine tool. Even though domestic and wild birds are evenly represented in the analyzed corpus, the domestic birds are semantically and metaphorically more productive. The contrastive analysis established that the majority of metaphors are based on anthropomorphism, and that pejorative terms, which serve to semantically derogate women, dominate over terms with positive connotations. We have found pejorative connotations and hints of sexism even in the case of terms of endearment, which are supposed to express a special intimacy and congeniality. Interlingual differences, in the sense of the existence of more specific meanings, are realized within the framework of age and sexual connotation. The interlingual and intralingual variations (Kövecses, 2005, 2015) are the result of the dependency of metaphorical meaning on context and participants in the communication process.